A multifunctional bilayer wound dressing co-loaded with nanosilver and bFGF for enhanced skin regeneration: synergistic antibacterial, hemostatic, and angiogenic effects - Wang, Qianqian; Ma, Fang; Xian, Ying; Shi, Xingyan; Ma, Shenglan; Zhang, Rui; Zhang, Hualin (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionWound closure, infection prevention and accelerated healing are important to consider in the development of multifunctional dressings. In this study, we aimed to design a dressing that can simulate the structure of normal skin, prevent bacterial infection, improve hemostasis and angiogenesis, accelerate cell adhesion and proliferation, and continuously promote skin regeneration.MethodsWe created a multifunctional bilayer dressing coloaded with nanosilver and basic fibroblast growth factor (bFGF) via emulsion electrospinning and vacuum freeze-drying methods. The upper hydrophobic layer was composed of a poly(lactic‐co‐glycolic acid)/wool keratin (PLGA/WK) electrospun membrane containing nanosilver and bFGF, and the lower hydrophilic layer was composed of a chitosan sponge containing bFGF.Results and DiscussionThe bilayer dressing allowed the sustained release of nanosilver and bFGF for more than 2 weeks, had good water absorption and water retention rates, had an appropriate water vapor transmission rate, absorbed excess exudate, and maintained a moist wound environment. In vitro, the dressing prevented bacterial penetration, accelerated fibroblast migration, and promoted angiogenesis and coagulation. Furthermore, the bilayer dressing facilitated cell migration and proliferation, promoted vessel formation, shortened the healing time and significantly promoted wound healing in vivo. By day 3, the wound healing rate in the bilayer dressing group (35.28% ± 2.06%) was significantly higher than that in the control group (23.99% ± 4.32%), representing an increase of approximately 47%. Our findings suggest that this multifunctional bilayer dressing coloaded with nanosilver and bFGF is a potential candidate for skin repair and regeneration applications.